The Technology of Corn Processing as an Effort to Increase The Income of Kelambir V Village - Havena, Martos; Marlina, Leni (Journal of Saintech Transfer, 2018)
Majority of people in Kelambir V Kebon, Hamparan Perak Sub-district, Deli Serdang Regency work as farmers. Farmers in this area have been experiencing obstacles in marketing their yields if the results are abundant. To solve this problem, some activities will be conducted in the form of: (1) transfer of knowledge, such as lecture and discussion, (2) training, and (3) assistance on the corn processing techniques. The objectives and targets to be achieved through these activities including: (a) the farmers community or group can process their yields optimally, so that the quality is improved and food diversification program can run well, (b) the farmers and the local community in Kelambir V Village can perform the processing techniques of yields skillfully, so they can obtain additional income through the resulting products, (c) the farmers and the local community in Kelambir V Village can maintain health by making corn as an alternative main food product, (d) creating a cooperation between university and community in the form of community service, and (e) being a partner of government in the processing of crops (i.e. corn) into corn processing products to increase income of the farmers. The activities which have been done were location survey, lecture, the implementation of corn processing techniques into processed corn products named dodol, sustainable monitoring, and product marketing guidance.